Faktor Sosial Ekonomi dan Perilaku Makan Balita: Kajian Hubungan antara Pekerjaan Ibu dan Pendapatan Keluarga - Eka Putri Rahmadhani (Fakultas Kedokteran, 2025)
Eating behavior in toddlers is an essential factor in supporting the growth and development of early childhood, as this period represents the golden age that determines a child’s future health and intelligence. Poor eating patterns and behaviors may lead to nutritional problems, including both undernutrition and overnutrition, which can have long-term impacts on children’s health. One of the factors influencing toddlers’ eating behavior is the family’s socioeconomic condition, particularly the mother’s employment status and family income level. Mothers play a central role in regulating meal patterns and providing nutritionally balanced food for their children. This study aimed to determine the relationship between maternal employment and family income with eating behavior among toddlers aged 6-59 months in Pekon Klaten, Gadingrejo Subdistrict, Pringsewu Regency. The research employed a descriptive analytic design with a cross-sectional approach. The independent variables included maternal employment and monthly family income, while the dependent variable was toddler eating behavior. The data analysis showed a significant relationship between maternal employment and toddler eating behavior (p = 0.013), but no significant relationship between family income and toddler eating behavior (p = 0.442). These findings indicate that maternal involvement in childcare and feeding practices has a greater influence on toddlers’ eating behavior than family economic factors. Keywords: eating behavior, toddlers, maternal employment, family income, socioeconomic factors